Management compensation and earnings-based covenants as signaling devices in credit markets - Levine, Carolyn B.; Hughes, John S. (Journal of Corporate Finance, 2005)
A firm seeks to raise capital in credit markets to fund risky operating activities. The firm has private information about the future cash flows from such activities. Firm owners delegate operating decisions to a manager who privately learns further information about the distribution of those cash flows subsequent to contracting, but before taking actions. Those actions include the selection of which operating activities to pursue and how much hidden effort to exert. At issue initially after introducing the problem is the efficient design of the manager's compensation as a device for signaling private information to lenders as well as for inducing operating decisions. Our results provide conditions under which a Bayesian Nash separating equilibrium satisfying the Cho–Kreps intuitive criterion exists. Broadly speaking, these results suggest that contracts that resolve internal adverse selection and moral hazard problems may serve as signaling devices in efficiently resolving information asymmetries with external parties. Next, we show how earnings-based debt covenants and the selection of conservative accounting methods may eliminate signaling costs altogether.